Combustion of avocado crop residues: effect of crop variety and nature of nutrients - Paniagua, Sergio; Reyes, Sergio; Lima, Francisco; Pilipenko, Nadezhda; Calvo, Luis F. (Elsevier, 2021)
The thermal behaviour of avocado crop residues was studied. The seeds and the pruning remains from Hass and Bacon varieties were analysed to know their fuel properties. The influence of the fertiliser nature was also studied thorough the application of cow manure and inorganic products. Thermogravimetric analysis (TGA) was carried out under 10, 20 and 40 °C/min heating rates. Kinetics was also estimated according to the Friedman, Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) methods. Results indicated the good fuel performance of the samples. Higher heating values (HHV) were higher for pruning remains (19.43 MJ/kg) when compared to seeds (18.74 MJ/kg). Cow manure improved the behaviour of all avocado samples regardless of the varieties. Average action energy was lower for wood (143.89–211.04 kJ/mol) than seeds (174.05–279.99 kJ/mol). Regarding TGA, this analysis showed three different mass loss associated to hemicellulose, cellulose and lignin release. TGA profiles were so different for the analysed biomass sources according to the fertiliser employed. Hence, the heating rate influenced the thermal behaviour of the samples, highlighting the fast release of the SBC and WHM for the 10 and 20 °C/min ramps respectively.
Keywords: Aguacates - Cultivo; Avocado crop residues; Bacon; Combustion; Fertiliser influence; Hass; Kinetics